Clinical evaluation of retrievable inferior vena cava filters for the prevention of pulmonary thromboembolism - Hirano, Shojiro; Funatsu, Atsushi; Nakamura, Shigeru; Ikeda, Takanori (Heart and vessels, 2021)
Background and aims Inferior vena cava filters (IVCFs) have been reported to cause chronic complications. Recently, retrievable IVCFs (r-IVCF) have been increasingly used to prevent acute pulmonary thromboembolism (PTE) and allow retrieval upon reduction of PTE risk. However, the outcomes of their use in Japan remain unknown. Methods This study retrospectively investigated the acute PTE relapse prevention rate, IVCF retrieval attempt rate, retrieval success rate, and long-term prognosis of 197 patients who underwent r-IVCF insertion at our hospital between 2010 and 2018. Results Subjects had a mean age of 68 years and a male-to-female ratio of 1:1. After r-IVCF insertion, the acute PTE prevention rate was 99.5%. The r-IVCF retrieval rate was 55% (108 patients), with a success rate of 99% (107 patients). r-IVCF retrieval was not attempted in 89 cases due to advanced cancer or poor prognosis (41%), loss to follow-up (32%), and long-term indwelling IVCF (17%). The retrieval group had an average observation period of 36 months, with their anticoagulation therapy continuation, PTE recurrence, and deep vein thrombosis (DVT) recurrence rates being 64%, 3%, and 4%, respectively. The non-retrieval group had a mean observation period of 21 months, with their anticoagulation continuation, PTE recurrence, and DVT recurrence rates being 78%, 3%, and 15%, respectively. DVT recurrence rates increased significantly in the non-retrieval group ( p < 0.01). Moreover, 65% of all DVTs occurred centrally from the femoral veins, among which 9% were contraindicated for anticoagulation therapy. Conclusions IVCF placement significantly prevented acute PTE but promoted recurrent DVTs when not retrieved after risk reduction. Hence, to increase recovery rates, IVCFs be promptly removed when no longer necessary.